Educação para a vida: uma experiência metodológica - Ribeiro, Ivana de Campos (2003)
The deep crises, which we live in the social and natural environment, have their origin in the way we understand and act on them. The values that we give to theses environments not only reflect our way of thinking and acting, but also the way we try to solve the problems. The (Environmental) Education, in this sense, can contribute immensily. This work refers to the intervention made in a Primary school of Rio Claro city, state of São Paulo, with the teachers stuff as a way of preparing them to a methodological proposal, the Environmental Education of Body & Soul ,and its five stages model, whose main characteristic is to join cognitive experiences with emotional ones, through the utilization of animismmist activities, having the water as generator theme of transversatility. Its main goal is the inquiry of the applicability potential of the educators proposal, who developed their works together with the students. We expected to stimulate changing, in both teachers and students, in their manner of understanding and acting on the different environments that they live. After two years of intervention, we could see the applicability of this proposal on the part of the teacher whose major indicators were the results observed with the students. Among them: the highest rates of conceptual information retention were linked with the subjects that took more advantages of the animismmist activities, the favoritism of more pleasurable scholar environment, bigger interest and involvement in environmental matters; besides the perception of the connections among the subjects and their contents, favoring the net knowledge, collaborating to the knowledge unification. Other indicators of the positive effects are: the comprehension of the human being like part of the nature, where the human actions against the nature harm the own human; and, the valorization of our natural resources, demonstrated as phrases of affective contents.